The arts in Nazi Germany : continuity, conformity, change - Huener, Jonathan; Nicosia, Francis R., 1944- (Vermont studies on Nazi Germany and the Holocaust., 2006)
Culture and the arts played a central role in the ideology and propaganda of National Socialism from the early years of the movement until the last months of the Third Reich in 1945. Hitler and his followers believed that art and culture were expressions of race, and that "Aryans" alone were capable of creating true art and preserving true German culture. This volume's essays explore these and other aspects of the arts and cultural life under National Socialism, and are authored by some of the most respected authorities in the field: Alan Steinweis, Michael Kater, Eric Rentschler, Pamela Po.